Family caregivers support their patient's decision to participate in a phase 1 clinical trial: Weighing the pros and cons, bearing the costs. Issue 8 (29th April 2022) - Kogan, Naomi; Tolley, Michelle; Cohen, Robin
Abstract: Objectives: When patients with advanced cancer pursue phase 1 clinical trials, family caregivers are impacted as they adopt new roles and responsibilities in time‐pressured, uncertain circumstances. This study explored the nature of the caregivers' participation in patients' decision to pursue phase 1 clinical trials and the early impact of the decision on the caregiver. Methods: Semi‐structured interviews were conducted with 19 family caregivers of advanced cancer patients who had agreed to participate in phase 1 clinical trials. They were coded for information about the caregiver's relationship with the patient, typical style of decision‐making together, understanding of the patient's prognosis and trial, contributions to decision‐making and the initial impacts of the trial on the caregiver. Codes illuminating the research questions were grouped into categories and themes, compared across transcripts and examined against the literature. Results: Caregivers unequivocally supported the patients' decision to pursue the phase 1 trial as they hoped that the patient would derive medical benefit from the trial. They withheld their opinions and fears about the trial from the patients to support patient autonomy during the decision‐making process. The patient's decision to participate increased the caregivers' burdens and deprived them of time spent on pleasurable activities at end of life. Conclusions: Respecting the patients' personal autonomy, caregivers supported the trial, despite the complex caregiving required. As the success of phase 1 trials relies on caregiver involvement, it is imperative that healthcare professionals be sensitized to the support needs of these caregivers.